The Development of Management Education in 4.0 Era in Islamic School, West Java - Muhammad Ihsan Dacholfany; Ni Putu Ayu Kartika Sari Dewi; Bambang Ismaya; Suhardi Suhardi; Ratih Kusumastuti (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Education is one of the aspects that is favoured in advancing the country. In this case, education must be able to adjust its role along with the times. In this 4.0 era, every school community, teachers, lecturers, students and others can actively access and find learning resources. This research uses qualitative methods with data collection techniques through observation, interviews and documentation. The results of data collection are one of the obstacles in terms of the development of education management, including less qualified human resources and a stable internet network that can support accessing existing learning resources so that the impact is in the form of learning access sources on the internet that are still not many, and also welfare to teachers or educators and employees in schools. In addition, adequate equipment such as computers is also needed in education management to gain comprehensive access, both in accessing learning materials and gaining access to every question to carry out teaching and learning activities.